Influence of solid lubricants on tribological properties of polyetheretherketone (PEEK). (November 2016) - Rodriguez, V.; Sukumaran, J.; Schlarb, Alois K.; De Baets, P.
Abstract: This study is aimed to compare the tribological behaviour of solid lubricants in a polyetheretherketone (PEEK) polymer matrix under different contact pressures and sliding speeds on dry reciprocating conditions. PEEK from the tribological viewpoint presents relatively high friction coefficients during unlubricated sliding but the wear rates are remarkably low. Although, when some fibres reinforcement and lubricants are added to this polymer matrix the coefficient of friction reduces significantly but the wear behaviour is indeterminate. From tribological tests, PEEK polymer matrix generates a transfer film in the countersurface which influences wear rate. A mathematical model based on dimensional analysis was performed to determine the influence on transfer polymer film formation. This was defined in terms of operating conditions, compositions and roughness. Highlights: The tribological behaviour of neat and filled PEEK in sliding contact is compared. Transfer film formation was examined by dark field imaging and optical microscopy. Transfer film area was calculated by segmentation technique. The calculated area was used in the analytical model. A mathematical model was developed based on a dimensional analysis.